Senojo geležies amžiaus (I-IVa.) metaliniai žiedai - Stankevičius, Mantas (Archaeologia Lituana, 2007)
Introduction. The Old Iron Age is a period when the number of metal articles in Lithuania increases. Adornment groups increase as well. Metal rings from the Old Iron Age are a group of adornment getting the least researchers’ attention among all the adornment groups of this period. Some attention was given only to exclusive rings. Namely, it was the lack of archeologists’ attention that encouraged to launch this subject. The task of this work was to get acquainted with typology of metal rings, to explore their decoration, try to restore the production of metal rings but the main thing was to collect as much as possible the best part of information and to publish it. In all, the database stores rings dating back to the Old Iron Age.Typology. Typology of rings was first mentioned in “Lithuanian archeological material” by Tarasenka published in 1928. In 1961 P. Kulikauskas describing rings, distinguished a group of sash rings varying according to the cross-section of the wire used for their production. Such rings date back to 2nd-3rd century. Spiral ring group is also divided into varieties according the cross-section of the strip: round (dating back to 2nd-3rd century), triangle. The author attributes “rings with rosette eye” to the third group. They are dated back to the 2nd-3rd c. as well. One of the major events in the typology of rings was Ch. Beckmann’s work “Metilfingerringe der romischen Kaiserzeit im freien Germanien” published in 1969 where she tried to classify all the known rings into groups, types. Namely, it was this work which greatly served Lithuanian archeologists while writing and speaking about rings. The Baltic material from Lithuania was also used in compiling this typology. 8 rings found in burial-grounds of Western Lithuania were also included into the catalogue. Typology was created having 844 items of rings. It is not a great number, having in mind that it was created the whole typology which has been used by almost all Europe for a long time. Some of the groups / types distinguished by the author, to my mind, are not numerous to be distinguished into a type or even a group. In 1986 M. Michelbertas in his study “The Old Iron Age in Lithuania” on the basis of Ch. Beckmann typology, grouped the Old Iron Age rings existing in Lithuanian archeological material. Archeologist. In my opinion the most appropriate typology of the rings from “the Old Iron Age” would be as follows:I group - spiral rings (1. with a widened middle curl; 2. plain spiral rings)II group - sash rings (1. closed; 2. open)III group - rings with overlapping terminals. There is a deep typological gap here - some archeologists distinguish 1.3 curl rings, others consider the same rings as overlapping terminals. The rings in this work are represented the way archeologists entitled them earlier, though in the future I think there should be determined “overlapping” boundaries. There are also might be some troubles speaking about typological differences between open sash rings and overlapping terminal rings. It happens that terminals of the open sash ring overlap too but here there is a small difference, in case of the rings with overlapping terminals their terminals don’t make horizontal line overlapping - most often they are above each other.IV group - rings with unconverged terminals. This term is created by archeologists to name the rings from Palanga or Rūdaičiai. They could be classified as open sash rings but I haven’t done it this time as there should be a common agreement among all the archeologists.V group - signet rings. Not many of them are found in The Old Iron Age burial grounds and they are not so typical as distinguished by Ch. Beckmann.VI group - cruciform rings. The term suggested by M. Michelbertas is used to describe rings decorated by five circles in the front part. I think it is an appropriate term as before we also used to have cruciform pins in findings typology.Rings. In the graveyards dating back to the Old Iron Age one can find spiral, sash rings, rings with overlapping terminals, unconverged terminals, rings with wreathed-twisted front part, cruciform and signet rings. Their diameter used to be 1.3-3.2 cm, height - 0.5-1.7 cm. Even 97% of the rings were made of brass. There were found only 14 silver rings (4 spiral, 3 sash, 6 with overlapping terminals, 1 with a wreathed-twisted front part). Rings belonging to different groups are often found in one grave.Spiral rings were found in women’s graves, on the average 1.29 spiral ring in a grave. Whereas, in men’s graves there were found only 42 spiral rings, on the average 0,91 spiral ring for a buried person. The number of spiral rings found in the graves ranges from 1 to 6. Spiral rings were twisted of triangle, half-round and square cross-section strips or round cross-section wire. The rings twisted of round cross-section wire were manufactured by using wire 0.1-0.5 in diameter, triangle cross-section - 0.15-0.35 cm wide and 0.09-0.18 cm thick; half-round - 0.14-0.4 cm wide and strip 0.07-0.2 cm thick. In the graves dating back to the Old Iron Age spiral rings are found with 1 to 9 curls. 12 spiral rings distinguish themselves from other rings of this period by having flattened terminals. Such rings are found in Dauglaukis, Upytė, Žviliai. 12 spiral rings are found with widened middle spiral in the front part (Ch. Beckmann’s type 37). It is believed that in Lithuania these types of rings were started to wear in the first part of the IV century. Spiral rings with interwoven tugs were found in Baitai, and Žviliai. Interweaving technique in Lithuanian archeological material is more widely spread in the middle Iron Age. In Lithuania there were found only 4 spiral rings made of silver in Baitai, Pavajuonys-Rėkučiai, Užpelkiai.Sash rings. The facts suggest that in women’s graves there were found 26 sash rings, on the average 0.34 in a grave. The graves in which the buried person was identified as a masculine there were found only 21 sash ring, on the average 0,46 sash ring in a grave. In the graves of the Old Iron Age there were found from 1 to 6 rings. Sash rings might be divided into closed (Ch. Beckmann distinguished as a first group) and open ones (according to Ch. Beckmann belonging to 5th group).The facts suggest that closed sash rings were found in Kurmaičiai, Marvelė, Paulaičiai, Rūdaičiai, Strazdai-Ječiškiai, Vėžaičiai, Žviliai, open sash rings were found in Dauglaukis, Eiguliai II, all the found sash rings are open in Marvelė, Žviliai. According to A. Tautavičius open sash rings were worn in the middle-end of the 1st century A.D. Sash rings in the Old Iron Age were manufactured of square (0.6-1.66 cm wide and 0.05-0.07 cm thick strip), half-round (cross-section strips 0.45-1.8 cm wide and 0.1-0.56 thick), triangle (strips 0.8-1.06 cm wide and 0.24-0.3 thick), convex cross-section strips and round section wire (wire 0.155-0.42 cm in diameter). The earliest sash rings are considered to be made of square cross-section strips. In Sargėnai and Kurmaičiai there were found 3 sash rings with openwork front part (Ch. Beckmann 26). According to M. Michelbertas they were probably worn in B2 / C1-C2 periods. Three sash rings (Dauglaukis, Marvelė) were made of half-round section 1st group bracelets. In disposable material there are only 3 sash rings made of silver (Lazdininkai, grave 57, Marvelė, grave 1186 and Žviliai, grave 91).Rings with overlapping terminals. The rings with overlapping terminals distinguished by archeologists were found in Baitai - graves 7, 8, 14, 18, 38, Gintarai - grave 20, Jagminiškė, Marvelė - grave 1269, Pavajuonys-Rėkučiai - barrow XI, grave 2, Pėžaičiai - grave 3, Santaka - barrow II, grave 1, Sargėnai - grave 37, 242, 323, Užpelkiai - grave 14, Žviliai grave 87, 99, 275, 295. It is possible that these rings are reflection of Roman rings with zoomorphic terminals (in Ch. Beckmann typology type 42) manufactured by the Old Iron Age Western Lithuanian jewelers. The perfect example of which is a ring with overlapping terminal found in Baitai - grave 38. Its terminals are sort of a snake’s head. 1 to 4 such rings are found in the graves. The rings with overlapping terminals were manufactured of round cross-section wire, half-round and square cross-section strips. Silver rings with overlapping terminals were found in Baitai - grave 14, Pavajuonys-Rėkučiai - barrow XI, grave 2 (3 rings), in Žviliai - grave 87 (2 rings).Rings with unconverged terminals. Rings group with unconverged terminals is also distinguished in Lithuanian archeological material. These are the rings that should be attributed to Ch. Beckmann’ group 5. Such rings were found one at a time In Baitai - woman’s grave 21 and area 2, Dauglaukis - grave 103, Palanga, Baltic square - grave 17 and Žviliai man’s grave 259. It is believed that such rings in Lithuania were uncommon (it’s still reflected in archeological material), some of them were worn from 2nd-3rd till 11th-12th century, S. Laul dates back such rings to IV century in Estonia.Rings with wreathed-twisted front part. A group of rings with wreathed-twisted front part corresponding to Ch. Beckmann’s type 22c is also distinguished. Such rings were in Bandužiai grave 63, 74 and Lazdininkai - grave 70. Both rings were found in women’s graves in Lazdininkai, the same silver ring - in man’s grave. The rings date back to 2nd-3rd century according to the material of Lazdininkai necropolis.Cruciform rings. Rings with cruciform front part otherwise cruciform rings are found among Old Iron Age findings. Such rings were found in Dauglaukis - woman’s grave 110, Stragnai and Šarkai - grave 30. According to E. Jovaiša this ring is not just a ring it is symbol of power, regalia. Rings date back to 2nd-3rd century.Signet rings. A ring with widened front part, ending up with a round notch ornamented plate 1.3 cm in diameter found in Barzūnai - grave 16 should be attributed to signet rings as well as rings in Dauglaukis - grave 103 and Užpelkiai, grave 33. Grave 33 dates hack to 3rd-4th century.Decoration. 66 rings it makes up only 16% of all rings found in Old Iron Age burial monuments are ornamented. There were found 40 spiral rings, 61% of all ornamented rings, 13 sash rings (19%), 13 rings with overlapping terminals (19%) and ring fragment (1%).Manufacture. It takes about 5 minutes to produce a spiral ring. The question is if it was worth bringing brass sticks in order to produce a decoration. The rings found in burial monuments prove that they had been used as decoration (found with finger bones segments or at the bracelets) But we also can’t totally reject Ch. Beckmann’s hypothesis that spiral rings could have been the way of payment - some kind of currency unit, especially it concerns the most primitive rings.For conclusion. Ch. Beckmann’s typology of rings is not quite appropriate for Lithuanian archeological material. The typology of this group of decoration should be improved in Lithuania. In the Old Iron Age metal rings in Lithuania already appears in B1 period. They are more abundant in periods C1a-C2.The improvement of the ring manufacture technique might be compared with the appearance of spiral rings with widened front part - C3 - periods. It’s hard to say which group of rings appeared earlier in the territory of Lithuania, archeological material possesses rather simple open sash rings as well as the most primitive spiral ones. In the collected material there are 7 rings, all of them spiral ones, dating back to the first centuries of the era. Appearance of sash rings dates back to B2 / C1 period.Metal rings were worn by men as well as women in the first centuries A.D. Spiral rings are more numerous in women’s graves, sash ones - in men’s graves. Decedents were buried with 1-6 rings. Not always rings found in the graves belonged to the same group.It may be that rings in the Old Iron Age were one of the indicators showing one’s social position. The example of this may be cruciform rings which are found only 3 as yet; Metal rings of the Old Iron Age are mostly found in laminar burial grounds of the Western part of Lithuania, in the barrow territories and in the lower reaches of the river Nemunas.The decoration of metal rings in the Old Iron Age is not complicated. The most popular is vertical hack motive. The manufacture of rings was not complicated in the first centuries A.D.Only cruciform, signet and rings with unconverged terminals are distinguished by more complicated elements of decoration. The rings are apparently manufactured in Lithuania. Though jeweller’s workshops are not detected in Lithuania but judging by the rings which are considered to be smarter copies of rings manufactured outside the Baits territory we can guess that the articles are manufactured by local masters.